Nilai Etis Dalam Sistem Kekerabatan Jepang - Sri Sudarsih (KIRYOKU, 2020)
This study aims to formulate ethical values in the Japanese kinship system. This ethical value is reflected in the Japanese family spirit. This research is a qualitative research in philosophy. The material object is the Japanese kinship system, while the formal object is an ethical value. The method used in this research is description and interpretation. The results achieved were formulated as follows: the kinship system of Ie became a model of preserving traditional values inherited from ancestors. These values are universal, namely the sense of kinship in which there is a sense of love, belonging and pride. Kachou as a role model is central in preserving this value. These values can also be transferred into modern management by reinterpretation according to place and time.